Simple, Sensitive and Rapid LC/MS/MS Method for Quantification of Residual Phenylbutazone in Milk - KUMAR BALIYAN, PRAVEEN; TYAGI, REENA; SINGH, R.P.; ARORA, SAURABH (Asian Journal of Chemistry, 2010)
A simple, sensitive and rapid liquid chromatography mass spectrometry method was developed and validation for estimation of residual phenylbutazone in milk. An analyte was extracted by liquid-liquid extraction with dichloromethane. A chromatographic separation was performed on reversed phase chromatography C-18 column with mobile phase 0.3 % formic acid in water and 0.3 % formic acid in methanol. The analyte was quantitated in positive ionization by mass spectrometer. The mass transitions m/z 309.3 > 162.1, 309.3 > 160.1, 309.3 > 146 and 309.3 > 104.0 were used. The lower limit of quantification was 1.0 ng/g with relative standard deviation of less then 15 %. The average recovery of phenylbutazone in milk fortified at the level of 1.0 ng/g was 77.38 % with relative standard deviation of 5.76 %.